RNF213 p.R4810K (c.14429G > A) Variant Determines Anatomical Variations of the Circle of Willis in Cerebrovascular Disease - Eto, Futoshi; Yoshimoto, Takeshi; Okazaki, Shuhei; Nishimura, Kunihiro; Ogura, Shiori; Yamaguchi, Eriko; Fukuma, Kazuki; Saito, Satoshi; Washida, Kazuo; Koga, Masatoshi; Toyoda, Kazunori; Morimoto, Takaaki; et al. (Frontiers in Aging Neuroscience, 2021)
Introduction Dysregulation of the RING finger protein 213 (RNF213) gene impairs vascular formation in experimental animal models. In addition, vascular abnormalities in the circle of Willis are associated with cerebrovascular disease. Here, we evaluated the relationship between the East Asian founder variant RNF213 p.R4810K and consequent anatomical variations in the circle of Willis in cerebrovascular disease. Patients and Methods The present study is an observational cross-sectional study. It included patients with acute anterior circulation non-cardioembolic stroke admitted to our institution within 7 days of symptom onset or last-known-well from 2011 to 2019, and those who participated in the National Cerebral and Cardiovascular Center Biobank. We compared anatomical variations of the vessels constituting the circle of Willis between RNF213 p.R4810K (c.14429G > A) variant carriers and non-carriers using magnetic resonance angiography and assessed the association between the variants and the presence of the vessels constituting the circle of Willis. Patients with moyamoya disease were excluded. Results Four hundred eighty-one patients [146 women (30%); median age 70 years; median baseline National Institutes of Health Stroke Scale score 5] were analyzed. The RNF213 p.R4810K variant carriers (n = 25) were more likely to have both posterior communicating arteries (PComAs) than the variant non-carriers (n = 456) (56% vs. 13%, P < 0.01). Furthermore, variant carriers were less likely to have an anterior communicating artery (AComA) than non-carriers (68% vs. 84%, P = 0.04). In a multivariate logistic regression analysis, the association of RNF213 p.R4810K variant carriers with the presence of both PComAs and the absence of AComA remained significant. Conclusion Our findings suggest that the RNF213 p.R4810K variant is an important factor in determining anatomical variations in the circle of Willis.